Kegiatan Peningkatan Literasi Fintech Peer To Peer Lending Syariah sebagai Permodalan UMKM Sidoarjo - Fitri Nur Latifah; Novia Ariyanti; Imam Fauji; Nuris Tiswanah; Lukita Nova Azzara (J-ABDIPAMAS (Jurnal Pengabdian Kepada Masyarakat), 2023)
ABSTRACT Technological developments are very massive in Industrial 4.0 era including in the economic and financial fields. Disruptions in the financial sector include the emergence of fintech with several schemes including sharia peer to peer lending in providing financial services to the community. MSMEs are included in the economic pillars of important economic growth in all countries in the world, and capital issues occupy the most important position in the development of MSMEs themselves. The many obstacles when wanting to apply for funding to MSME banking are often constrained by several document requirements for submission which makes MSMEs unable to access capital from banks (unbankable), so this syaraiah peer to peer lending fintech platform is an alternative capital for MSMEs. However, there were concerns that there was cybercrime in accessing the platform, which made our team tapped to carry out activities to increase peer to peer lending sharia fintech literacy for MSMEs in Sidoarjo. Our activities begin with observing partner needs, program preparation, followed by outreach, training and assistance to MSMEs, ending with program evaluation. Evaluation of this program was carried out by giving a pre-test before training program and conducting a post-test after training program. The results showed a significant increase in Sharia peer to peer lending fintech literacy of around 50%.  Keywords: Literacy; disruptiv, Fintech; Sharia peer to peer lending, MSME Capital ABSTRAK Dalam perkembangan dunia di era industrai 4.0, perkembangan teknologi sangat masif termasuk di bidang ekonomi dan keuangan. Disrupsi di bidang keuangan diantaranya munculnya fintech dengan beberapa skema termasuk peer to peer lending syariah dalam memberikan pelayanan keuangan bagi masyarakat. Bidang usaha UMKM adalah termasuk pilar ekonomi dalam pertumbuhan ekonomi yang penting di semua negara di Dunia, dan permasalahan permodalan menempati posisi paling utama dalam perkembangan UMKM itu sendiri. Banyaknya kendala ketika ingin mengajukan pendanaan ke perbankan UMKM sering terkendala beberapa kebutuhan dokumen untuk pengajuannya yang menjadikan UMKM tidak bisa mengakses permodalan dari penbankan (unbankable), sehingga platform fintech peer to peer lending syaraiah ini merupakan sebuah alternatif permodalan bagi UMKM. Namun ada kendala kekhawatiran adanya cybercrime  didalam mengakses platform tersebut membuat tim kami terketuk untuk membuat kegiatan peningkatan literasi fintech peer to peer lending syariah bagi UMKM di Sidoarjo. Kegiatan kami diawali dengan observasi kebutuhan mitra, persiapan program, dilanjutkan dengan sosialisasi, pelatihan dan pendampingan kepada UMKM diakhiri dengan evaluasi program. Evaluasi program ini dilakukan dengan memberikan pre-test sebelum kegiatan dan melakukan post-test setelah kegiatan, didapatkan hasil adanya peningkatan signifikan terhadap literasi fintech peer to peer lending Syariah sekitar 50%. Kata Kunci: Literasi, Disruptive; Fintech, Peer to peer Lending syariah Permodalan UMKM